MENIMBANG MADRASAH DINIYAH TAKMILIYAH SEBAGAI PENGUAT PEMBINAAN AKHLAK MULIA ANAK-ANAK DARI KELUARGA KARIER - Rinda Fauzian (Tatar Pasundan : Jurnal Diklat Keagamaan, 2021)
The role of Madrasah Diniyah Takmiliyah is quite essential in shaping Muslims, especially for children of career families. This research aims to identify and elaborate its role in terms of developing noble morals over industrial environments and career families. The approach used is qualitative approach with case studies. The results include: (1) the madrasah gives a positive role in forming individual to have faith, taqwa, and noble character as the spiritual foundation of learners in facing global community, (2) the madrasah is an alternative solution to religious problems for those who are living in the industrial environments and career families. After being observed, this madrasah plays an important role in forming students to have strong faith, honesty, responsibility, intellect, creativity, independency, religiosity, discipline, and social care. Keywords: Madrasah; Diniyah Takmiliyah; Career Families